QRIS Optimization for Micro Banking Customers to Increase Low Cost Fund at BSI Cimahi (Case Study of PT Bank Syariah Indonesia Cimahi Branch) - Agung Pramono; Marimin Marimin; Mimin Aminah (Politeknik Siber Cerdika Internasional, 2026)
Background: QRIS, Indonesia’s unified national digital payment standard, was introduced to promote financial inclusion and transaction efficiency. However, adoption among micro banking customers remains suboptimal due to limited digital literacy, uneven merchant coverage, and competition from fintech-based e-wallet platforms. Objective: This study aims to develop an optimization strategy to enhance QRIS adoption among micro banking customers of PT Bank Syariah Indonesia (BSI) Cimahi Branch, with a focus on increasing the Low Cost Fund (LCF) portfolio. Methods: This study employed a mixed-methods descriptive-analytical approach. Primary data were collected from 179 micro banking customers through observations, in-depth interviews, and questionnaires, supplemented by expert judgment from bank management and regulators. Secondary data included internal financing reports and official publications. Strategic analysis was conducted using the IFE, EFE, SWOT, IE Matrix, QSPM, and AHP methods. Results: The findings indicate that the IFE score of 2.60 and the EFE score of 2.38 placed BSI Cimahi Branch in a “Hold and Maintain” strategic position. Among the alternative strategies identified, the WO strategy—focused on improving digital literacy and optimizing QRIS usage through structured training and merchant assistance programs—obtained the highest Total Attractiveness Score (TAS = 6.24) and was confirmed as the priority strategy by AHP, with a global weight of 0.3498. Conclusion: The prioritized WO strategy supports the sustainable growth of LCF transaction volume, average account balances, and the Micro Banking segment at BSI Cimahi Branch by addressing the core barrier of inadequate digital literacy among micro merchants.